2008
DOI: 10.1038/ejhg.2008.89
|View full text |Cite
|
Sign up to set email alerts
|

Clinical phenotype of germline RUNX1 haploinsufficiency: from point mutations to large genomic deletions

Abstract: Germline RUNX1 mutations result in a rare autosomal dominant condition characterized by qualitative and quantitative platelet defects and predisposition to the development of myeloid malignancies (familial platelet disorder with propensity to acute myeloid leukaemia, FPD/AML). Only 13 pedigrees have previously been described so far. We report on two novel germline RUNX1 mutations: (1) an out-of-frame 8 bp heterozygous deletion (c.442_449del) in an FPD/AML pedigree and (2) a de novo 3.5 Mb deletion in the 21q22… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
80
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(89 citation statements)
references
References 17 publications
8
80
0
1
Order By: Relevance
“…[28][29][30][31][32][33][34][35][36] All but one case 32 reported thrombocytopenia, with qualitative platelet defects described in 2 cases. 30,36 MDS/AML developed in 3 cases, with a median age of onset of six years (range 5-8 years). This median age is much lower than that of traditional FPD/AML and suggests that other genes within the 21q22 locus may also be important in leukemogenesis.…”
Section: Syndromic Cases Of Loss Of Chromosome 21q22mentioning
confidence: 99%
“…[28][29][30][31][32][33][34][35][36] All but one case 32 reported thrombocytopenia, with qualitative platelet defects described in 2 cases. 30,36 MDS/AML developed in 3 cases, with a median age of onset of six years (range 5-8 years). This median age is much lower than that of traditional FPD/AML and suggests that other genes within the 21q22 locus may also be important in leukemogenesis.…”
Section: Syndromic Cases Of Loss Of Chromosome 21q22mentioning
confidence: 99%
“…Rare cases reporting intragenic deletion of RUNX1 gene or duplication of the chromosome 21 carrying the RUNX1-deleted or mutated allele may have similar phenotype. [29][30][31] A recent study indicated that familial platelet disorder should be suspected in AML cases with a RUNX1 biallelic mutation or with a single RUNX1 mutation with a variant allele frequency more than 50%, which could indicate trisomy 21 with a duplication of the mutated chromosome or loss of heterozygosity.…”
Section: Myeloid Neoplasms With Germline Runx1 Mutationmentioning
confidence: 99%
“…6 These data suggest that the 5q-syndrome represents a disorder of aberrant ribosome biogenesis. 3,6 Erythroid progenitor cells have a very high rate of proliferation and a requirement for massive globin synthesis, thus necessitating a very high level of ribosome biogenesis and ribosomal activity. This may explain the particular sensitivity of the erythroid lineage to reduced expression levels of ribosomal proteins.…”
Section: Conflict Of Interestmentioning
confidence: 93%
“…Constitutional deletions spanning RUNX1 have been reported in isolated congenital or syndromic thrombocytopenia, stipulating copy number analysis (CNA) of RUNX1 next to sequencing. [5][6][7][8] Given clinical heterogeneity, vigilance in diagnosing FPD/AML is required, reducing the risk of stem cell transplantation (SCT) with carrier siblings. 2,3 Furthermore, the identification of a RUNX1 abnormality and the elucidation of the underlying pathogenomic mechanism may have implications for genetic counseling for recurrence risk of FPD/AML.…”
mentioning
confidence: 99%